A Brief Survey of the Work Being Performed by Crisis Organisations in European Union Member States on Climate Change Effects. (19th February 2017) - Wester, Misse; Mobjörk, Malin
Abstract : The negative effects of climate change are calling for action to mitigate and adapt to future challenges. National crisis management authorities need to prepare to handle crisis caused by direct or indirect effects. In this study, we investigate how crisis management authorities within the European Union prepare for the effects of climate change by conducting a small questionnaire study. The questionnaire used consisted of 12 questions and was answered by 17 counties. Results indicate that most crisis management agencies focus on weather‐related incidents, such as floods, heatwaves and forest fires. Indirect effects are not prepared for to the same extent. The gulf between crisis management and climate adaptation is discussed.